2015
DOI: 10.1152/japplphysiol.00564.2014
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent hypoxia: a low-risk research tool with therapeutic value in humans

Abstract: Intermittent hypoxia has generally been perceived as a high-risk stimulus, particularly in the field of sleep medicine, because it is thought to initiate detrimental cardiovascular, respiratory, cognitive, and metabolic outcomes. In contrast, the link between intermittent hypoxia and beneficial outcomes has received less attention, perhaps because it is not universally understood that outcome measures following exposure to intermittent hypoxia may be linked to the administered dose. The present review is desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
102
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(110 citation statements)
references
References 161 publications
4
102
0
1
Order By: Relevance
“…Some characteristics of different regimes are described in recent reviews [4,5,7,8,12,13]. Historically, first methodical recommendations for IHT implementation in human practice were published by the Russian Health Ministry in 1988 which recommended the inhalation of 10-12% O 2 during 5-min periods with 5 min rest, 1 h per session, 1-4 weeks per course for the treatment of various diseases.…”
Section: Regimes Of Iht With Hypoxic Gas Mixtures Inhalation: Recommementioning
confidence: 99%
See 3 more Smart Citations
“…Some characteristics of different regimes are described in recent reviews [4,5,7,8,12,13]. Historically, first methodical recommendations for IHT implementation in human practice were published by the Russian Health Ministry in 1988 which recommended the inhalation of 10-12% O 2 during 5-min periods with 5 min rest, 1 h per session, 1-4 weeks per course for the treatment of various diseases.…”
Section: Regimes Of Iht With Hypoxic Gas Mixtures Inhalation: Recommementioning
confidence: 99%
“…Mechanisms of maladaptive responses are very good described in recent reviews [6,54,62,71,72, and many others]. Studies in this field have led to the view that intermittent hypoxia is the principal, if not the only, risk factor for the development of a number of detrimental cardiovascular, respiratory, metabolic, and cognitive outcomes [7]. The authors having analyzed a large number of studies concluded that protocols that were employed to establish the link between intermittent hypoxia and detrimental outcomes were typically severe in regards to intensity, duration, or both.…”
Section: Potential Side Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanisms underlying the beneficial effects of IHT have been investigated at the multiple biological levels, from systemic physiological reactions to genomic regulation. [1][2][3][4][5] The potential therapeutic uses of IHT in treating cerebrovascular and cardiovascular disorders have been the focal areas of extensive research. 6,7 Despite these advances, the effects of IHT on diabetes mellitus, especially type 2 diabetes, one of the most prevalent pathological conditions in the current world population, are much less investigated.…”
Section: Introductionmentioning
confidence: 99%